Preparation method of porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with multilevel structure and material

By combining adsorption method and photocatalytic method, electrospinning technology is used to construct a multi-stage structure of porous carbon nitride/aminoxime-based seawater uranium extracting composite material, the problem of limited adsorption sites of existing materials is solved and efficient and economical seawater uranium extraction effect is achieved.

CN119793419AActive Publication Date: 2025-04-11NANJING UNIV OF AERONAUTICS & ASTRONAUTICS

Patent Information

Application Number
CN202411961534.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing seawater uranium extraction materials have the problem of limited adsorption sites and easy to achieve saturation, which affects the adsorption capacity and uranium extraction efficiency.

Method used

By combining adsorption method and photocatalytic method, electrospinning technology is used to combine geminoxime-based fibers with carbon nitride photocatalytic materials to construct a multi-stage structure of porous, small-layer carbon nitride/geminoxime-based seawater uranium extracting composite material to enhance photocatalytic performance and adsorption performance.

Benefits of technology

It significantly improves the uranium adsorption performance and adsorption rate of seawater uranium extracting materials, solves the problem that nanomaterials are not easy to be recycled and used, and achieves efficient and economical seawater uranium extraction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793419A_ABST
    Figure CN119793419A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multilevel structure, and relates to the field of seawater uranium extraction materials. The composite material is a porous few-layer carbon nitride material with high photocatalytic performance obtained by repeatedly calcining melamine at a high temperature; polyacrylonitrile is subjected to amidoxime functionalization, and a polyamidoxime solution is obtained; uniformly dispersing porous few-layer carbon nitride in the polyamidoxime solution, and adding a sacrificial pore-forming agent polyvinylpyrrolidone at the same time to obtain a spinning solution; and finally, preparing the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with high adsorption performance by utilizing a one-step electrostatic spinning technology. The obtained composite material has excellent uranium adsorption performance and adsorption rate and can be recycled, the preparation method is simple in process and free of pollution to the environment, and the prepared composite material has excellent uranium adsorption performance and adsorption rate, can be recycled and has wide application prospects in the field of uranium extraction from seawater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of seawater uranium extraction materials, in particular to a preparation method and material of a porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure. Background Art

[0002] As a relatively green energy source, vigorously developing the nuclear power industry is an effective way to solve the global energy shortage and increasingly serious environmental problems. As the main fuel for nuclear energy, uranium resources on land are not abundant. The ocean contains a large amount of uranium resources, about 1,000 times the total amount on land. Extracting uranium from seawater and developing seawater uranium extraction materials are key means to ensure uranium resources for future nuclear energy development. In order to achieve high efficiency and economy in extracting uranium from seawater, seawater uranium extraction materials must have good adsorption capacity, adsorption rate, and recyclability.

[0003] Amidoxime-based fiber adsorbents have become the most important materials for uranium extraction from seawater due to their good affinity for uranyl ions and recyclability. For example, it has been reported that amidoxime-based fibers are used to adsorb uranium-containing wastewater. However, the uranium concentration in uranium-containing wastewater is relatively high (usually at the ppm level), while the uranium concentration in seawater is extremely low (~3.3ppb); there are toxic pollutants in uranium-containing wastewater, uranium exists in various forms (uranate, uranium fluoride, uranium oxide, etc.), and uranium in seawater mainly exists in the form of uranate. The materials used to treat uranium-containing wastewater in existing reports are not suitable for direct application in uranium extraction from seawater. In general, amidoxime-based materials prepared by existing methods generally have the problem of limited adsorption sites and easy saturation, which affects the adsorption capacity of the adsorbent material and the uranium extraction efficiency. Therefore, it is urgent to develop a new type of high-performance and sustainable uranium extraction material from seawater.

[0004] In the process of extracting uranium from seawater, external resources (such as light) can be used to make the reaction more economical and sustainable. In a highly dispersible C3N4-based seawater uranium extraction composite material and its preparation method disclosed in Chinese patent CN115228500A, the uranium removal rate of 5% Cring-WSGCN photocatalyst is 89.47%. A preparation method of a multifunctional uranium extraction material disclosed in CN118341398B, the carbon nitride-based material prepared can reach reaction equilibrium in about 40 minutes, and the adsorption amount reaches 52.1 mg / g. However, the carbon nitride material exists in the form of powder, which makes it difficult to handle and recycle, limiting its practical application. The powder adsorption material is compounded with a polymer matrix to overcome the disadvantage that a single powder material is difficult to recycle, but the particle size and content of the nanopowder can cause its agglomeration behavior in the polymer. This uneven load will reduce the effective specific surface area of ​​the outer surface of the material, thereby affecting the diffusion kinetics of uranyl ions on the adsorbent, resulting in a low adsorption capacity and a slow adsorption rate. Therefore, how to improve the adsorption performance of seawater uranium extraction materials has become a technical problem that needs to be solved in this field. Summary of the invention

[0005] In view of the above problems, the present application provides a method for preparing a porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure. The adsorption method is combined with the photocatalytic method to combine the amidoxime-based fiber with the carbon nitride photocatalytic material, and the photocatalyst and the polymer-based material are effectively compounded by the electrostatic spinning technology, thereby overcoming the problem that the prior art is difficult to achieve uniform loading of nanomaterials in the polymer substrate; by introducing porous few-layer carbon nitride, the photocatalytic performance of the composite material under visible light is enhanced; at the same time, by constructing a multi-level continuous adsorption channel, the mass transfer resistance is reduced, and the contact between the adsorbed liquid and the material is enhanced, thereby improving the uranium adsorption performance and adsorption rate of the seawater uranium extraction composite material.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] First, the present application provides a method for preparing a porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure, and the specific steps are as follows:

[0008] (1) calcining melamine in a sealed crucible at 550° C. for 2 h in a muffle furnace, and grinding the mixture after cooling to obtain yellow bulk carbon nitride powder; taking a certain amount of bulk carbon nitride and placing it in an ark under air atmosphere and sintering it in a muffle furnace at 550° C. to obtain white, fluffy, porous, few-layer carbon nitride;

[0009] (2) Mix hydroxylamine hydrochloride and N,N-dimethylformamide in a three-necked flask, and completely dissolve hydroxylamine hydrochloride in N,N-dimethylformamide by mechanical stirring (e.g., at a speed of 400 rpm), then add sodium hydroxide and vigorously stir (e.g., at a speed of 600 rpm) for 30 to 60 minutes; then add polyacrylonitrile powder and stir until the polyacrylonitrile is completely swollen (about 40 minutes), put it into an oil bath preheated at 80 to 90°C and continue to stir at a speed of 400 r / min, react for 12 to 18 hours, and after the reaction is completed, centrifuge to obtain a supernatant, which is the polyamidooxime solution;

[0010] (3) mixing the polyamidoximate solution, porous few-layer carbon nitride, and polyvinyl pyrrolidone, and performing ultrasonic dispersion and stirring to obtain a porous few-layer carbon nitride / amidoximate-based spinning solution;

[0011] (4) The prepared porous few-layer carbon nitride / amidoxime-based spinning solution is drawn and stacked by an electrospinning machine using the action of electric field force to prepare nanofibers, and the nanofiber composite material is immersed in an ethanol aqueous solution, immersed in methanol after soaking for a period of time, placed in a vacuum drying oven and dried to constant weight, and polyvinyl pyrrolidone is removed to obtain a porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure. The electrospinning technology used in this step is a conventional technology in the art, as disclosed in the document "Mishra KR, Mishra P, Verma K, et al. Electrospinning production of nanofibrous membranes [J]. Environmental Chemistry Letters, 2019, 17 (2): 767-800."

[0012] Preferably, in the preparation method of the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure, the heating rate of the block carbon nitride calcination in step (1) is controlled at 5 to 10°C / min, the heating rate of the porous few-layer carbon nitride calcination is controlled at 5 to 10°C / min, and the sintering time is 1 to 5 hours. The heating rate affects the degree of exfoliation of the carbon nitride nanosheets, and ultimately affects the photocatalytic reduction performance of the final product photocatalyst.

[0013] Preferably, in the preparation method of the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure, the mass volume ratio of hydroxylamine hydrochloride, sodium hydroxide and N,N-dimethylformamide in step (2) is preferably (2-4 g): (3-6 g): (40-50 mL). The mass volume ratio of polyacrylonitrile to N,N-dimethylformamide is (3-4 g): (40-50 mL).

[0014] Preferably, in the preparation method of the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure, the mass volume ratio of the polyamidoxime solution, the porous few-layer carbon nitride and the polyvinyl pyrrolidone in the step (3) is preferably 5 mL: (0.5-2 g): (0.05-0.25 g); the ultrasonication time in the step (3) is 15-30 min; and the stirring time is 12-16 h.

[0015] Preferably, in the preparation method of the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure, the electrospinning process parameters in step (4) are: at a temperature of 30°C and a humidity of 40%, the voltage is 10 to 25 kV, the needle is 10 to 20 cm away from the receiving plate, the injection pump speed is 0.2 to 0.5 mL / h, and the obtained fiber diameter ranges from 200 to 900 nm. Nanofibers have a large specific surface area that is conducive to providing more adsorption sites.

[0016] Furthermore, in the above step (4), the ethanol aqueous solution refers to an ethanol solution with a volume concentration of 30% to 50%, the immersion temperature is 45 to 55°C, and the immersion time is 12 to 24 hours. The immersion time in methanol is 3 to 7 days, and the temperature is room temperature. The drying condition is 90 to 100°C for 12 to 16 hours. Methanol immersion is used to remove the pore-forming agent polyvinyl pyrrolidone, thereby obtaining a porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material.

[0017] This application not only uses the amidoxime group to adsorb uranyl ions, but also breaks through the chemical adsorption equilibrium through photocatalytic reduction. At the same time, a multi-level structure is designed to reduce the mass transfer resistance in the mass transfer process, so that uranium and the adsorption site are in better contact, thereby promoting the combination of the chelating group amidoxime group and the uranyl ion, and achieving the purpose of further improving the adsorption performance; and, while using the amidoxime functional group for adsorption, the photocatalyst carbon nitride is introduced to convert the soluble U(VI) adsorbed to the amidoxime group adsorption site into insoluble U(IV), which can fall off after stirring, thereby releasing the adsorption site there, providing a position for the next adsorption, and improving the adsorption performance and adsorption rate. Compared with existing seawater uranium extraction materials, it has the following beneficial effects:

[0018] 1) The preparation process of the present invention is simple and easy to operate industrially.

[0019] 2) The present application scheme introduces polyvinyl pyrrolidone as a sacrificial pore-forming agent into the composite polymer spinning solution, and removes the polyvinyl pyrrolidone by simple soaking after the composite nanofibers are formed. On the one hand, the prepared amidoxime-based composite fibers for uranium extraction from seawater have a pore structure and a large specific surface area; on the other hand, as a dispersant, the particles can be effectively dispersed and stabilized.

[0020] 3) This application scheme uses a simple high-temperature calcination to peel off the bulk carbon nitride into porous few-layer carbon nitride nanosheets. The porous structure can improve the adsorption performance of the material, and the few layers can shorten the photogenerated electron-hole recombination path, improve the photocatalytic performance of the photocatalyst carbon nitride on uranium, and then improve the adsorption performance of uranium.

[0021] 4) The present invention adopts a one-step method to prepare a composite material for uranium extraction from seawater with a multi-level structure. The porous few-layer carbon nitride nanomaterial is loaded in the porous amidoxime-based fibers. On the basis of the macropores formed by interweaving the fibers, the microporous / mesoporous structure of the nanoscale adsorbent is further introduced to accelerate the infiltration of seawater, accelerate the adsorption of uranyl ions, and improve the adsorption rate. At the same time, the problem that the nanomaterials are difficult to recycle and easy to agglomerate is solved.

[0022] 5) The present invention uses electrostatic spinning technology to achieve stable loading of porous few-layer carbon nitride with photocatalytic properties in amidoxime-based nanofibers, and forms a multi-level structure seawater uranium extraction composite material. On the one hand, by constructing a multi-level continuous channel, the specific surface area of ​​the nanoscale fiber material is further increased, and the adsorption effect is further increased. On the other hand, the shortcomings of easy agglomeration and difficult recycling of photocatalyst powder are solved, and the uranium extraction capacity and selectivity of nanofibers are further improved, thereby obtaining a hierarchical structure nanofiber composite material with dual effects of adsorption and photocatalysis and efficient adsorption of uranium. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention is a flow chart for preparing the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material.

[0024] Figure 2 The synthetic route of amidoxime oximation liquid is as follows;

[0025] Figure 3 It is the Fourier infrared spectra of PAN (polyacrylonitrile) and PAO (polyamidoximine);

[0026] Figure 4 This is the microscopic morphology of the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material in Example 1:

[0027] Among them, a is a low-magnification (5000 times) SEM image of the composite material, b is a high-magnification (100,000 times) SEM image of the composite material, and c is a SEM image of the porous few-layer carbon nitride filler.

[0028] Figure 5 The uranium adsorption kinetics diagram of Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0029] The present invention is further described below with reference to specific examples. The raw materials, reagents, instruments, equipment, etc. involved in the examples are all commercially available products and can be purchased through commercial channels.

[0030] Example 1

[0031] The preparation process of the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material in this embodiment is as follows: Figure 1 As shown, the specific steps are as follows:

[0032] (1) 5 g of melamine was placed in a sealed crucible and heated to 550° C. at a heating rate of 5° C. / min and calcined for 2 h. After cooling, the mixture was ground to obtain a yellow powder, i.e., bulk carbon nitride. 0.5 g of the powder was then placed in an ark (60 mm×30 mm×15 mm) and heated to 550° C. at a rate of 5° C. / min in an air atmosphere and kept for 5 h. After the temperature was raised to 550° C. at a rate of 5° C. / min, porous few-layer carbon nitride was obtained.

[0033] (2) Mix 2g of hydroxylamine hydrochloride and 40mL of N,N-dimethylformamide (DMF) in a three-necked flask, stir at 400r / min with a mechanical stirrer. When the hydroxylamine hydrochloride is completely dissolved, add 3g of sodium hydroxide and stir rapidly at 600r / min for 30min. Then add 3g of polyacrylonitrile powder and stir at 400r / min for 40min until the polyacrylonitrile is completely swollen. Continue stirring at 400r / min for 12h at 80°C. After the reaction is completed, centrifuge at 8000r / min for 3 times, each time for 10min, and take the supernatant, which is the polyamidooxime solution. The synthetic route of this step is as follows: Figure 2 shown.

[0034] (3) The polyamidoxime solution prepared in step (2), the porous few-layer carbon nitride prepared in step (1), and polyvinyl pyrrolidone are mixed, and then ultrasonically dispersed (450W) for 15 minutes, and then stirred for reaction for 12 hours to obtain a porous few-layer carbon nitride / amidoxime-based spinning solution; the mass volume ratio of the added polyamidoxime solution, porous few-layer carbon nitride and polyvinyl pyrrolidone is 5mL:1g:0.1g.

[0035] (4) The prepared porous few-layer carbon nitride / amidoxime-based spinning solution is passed through an electrospinning machine (Huizhi Electrospinning Electrospinning Machine HZ-01) to draw and stack into nanofibers using the action of electric field force, and the composite nanofiber material is immersed in an ethanol aqueous solution (30% by volume) preheated to 45°C, maintained at 45°C for 12 hours, then taken out and immersed in methanol (purchased from Sinopharm Chemical Reagent Co., Ltd., AR grade, ≥99.5%), and immersed at room temperature for 3 days; finally, it is placed in a vacuum drying oven at 100°C for 12 hours to remove polyvinyl pyrrolidone, thereby obtaining a multi-level structured porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material.

[0036] In this step, the electrospinning process parameters are: temperature 30°C, humidity 40%, voltage 12kV, needle distance 10cm from the receiving plate, and injection pump speed 0.2mL / h.

[0037] Figure 3 The infrared spectra of polyamidoximine (PAO) prepared in step (2) of this embodiment and the raw material polyacrylonitrile (PAN) are shown in FIG. -1 There is a stretching vibration peak of -C≡N in PAN at 2248cm -1 The characteristic peak of -C≡N at 1653cm -1 and 931cm -1 New peaks appear at (derived from the stretching vibration peaks of -C=N and -NO in the amidoxime group, respectively), indicating the success of the amidoximation reaction.

[0038] The microstructure of the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material prepared in this example is as follows: Figure 4 As shown, a is a low-power (magnification of 5000 times) SEM image of the composite material, b is a high-power (magnification of 100000 times) SEM image of the composite material, and c is a SEM image of the porous few-layer carbon nitride filler prepared in step (1). The nanofibers in the composite material are evenly distributed, the diameter distribution is relatively uniform, the fiber morphology is good, and there is no phenomenon such as agglomeration and droplets, indicating that high-quality nanofibers are successfully prepared by electrospinning. Among them, the photocatalyst nanomaterial (porous few-layer carbon nitride) has good dispersibility and uniform distribution in the fiber, and the prepared porous few-layer carbon nitride / amidoxime-based composite material has a multi-level pore structure.

[0039] Example 2

[0040] 1) 5 g of melamine was placed in a closed crucible and heated to 550°C at a heating rate of 5°C / min in an air atmosphere and calcined for 2 h. After cooling, it was ground to obtain a yellow powder sample of block carbon nitride; 0.5 g of the powder was placed in an ark (60 mm×30 mm×15 mm) in an air atmosphere, and heated to 550°C at a heating rate of 5°C / min and calcined for 3 h. After the end, porous few-layer carbon nitride was obtained.

[0041] 2) 3 g of hydroxylamine hydrochloride and 45 mL of N,N-dimethylformamide (DMF) were mixed in a three-necked flask, and the hydroxylamine hydrochloride was completely dissolved by mechanical stirring at a speed of 400 r / min, and then 5 g of sodium hydroxide was added and stirred at a speed of 600 r / min for 30 min, and then 3.5 g of polyacrylonitrile powder was added and stirred at a speed of 400 r / min for 40 min until the polyacrylonitrile was completely swollen, and then stirred at a speed of 400 r / min for 15 h at 80° C. After the reaction was completed, the mixture was centrifuged at a speed of 8000 r / min for 3 times, each time for 10 min, and the supernatant was taken, which was the polyamidooxime solution;

[0042] 3) The polyamidoxime solution, porous few-layer carbon nitride and polyvinyl pyrrolidone are mixed, ultrasonically dispersed at 450W for 15 minutes, and then stirred for reaction for 12 hours to obtain a porous few-layer carbon nitride / amidoxime-based spinning solution; in this step, the mass volume ratio of the polyamidoxime solution, porous few-layer carbon nitride and polyvinyl pyrrolidone is 5mL:0.5g:0.05g.

[0043] 4) The prepared porous few-layer carbon nitride / amidoxime-based spinning solution is passed through an electrospinning machine and stretched and accumulated into nanofibers by the action of electric field force. The composite nanofiber material is immersed in an ethanol aqueous solution with a volume concentration of 40% preheated to 50° C. and maintained at 50° C. for 18 hours. Then, it is taken out and immersed in methanol at room temperature for 5 days, and finally dried in a vacuum drying oven at 100° C. for 14 hours to remove polyvinyl pyrrolidone, thereby obtaining a porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure.

[0044] The electrospinning process parameters of this example are: under an environment of temperature of 30° C. and humidity of 40%, the voltage is 15 kV, the distance between the needle and the receiving plate is 15 cm, and the injection pump speed is 0.3 mL / h.

[0045] Example 3

[0046] 1) 5 g of melamine was placed in a closed crucible and heated to 550° C. at a heating rate of 5° C. / min in an air atmosphere and calcined for 2 h. After cooling, it was ground to obtain a yellow powder, i.e., bulk carbon nitride. 0.5 g of the bulk carbon nitride powder was placed in an ark (60 mm×30 mm×15 mm) in an air atmosphere and heated to 520° C. at a heating rate of 5° C. / min and calcined for 3 h. After the completion, porous few-layer carbon nitride was obtained.

[0047] 2) Mix 4 g of hydroxylamine hydrochloride and 50 mL of N,N-dimethylformamide (DMF) in a three-necked flask, stir the hydroxylamine hydrochloride with a mechanical stirrer at 400 r / min until it is completely dissolved, then add 6 g of sodium hydroxide and stir at 600 r / min for 30 min, then add 4 g of polyacrylonitrile powder and stir at 400 r / min for 40 min until the polyacrylonitrile is completely swollen, continue stirring at 400 r / min for 18 h at 90°C, and after the reaction is completed, centrifuge at 8000 r / min for 3 times, each time for 10 min, and take the supernatant, which is the polyamidooxime solution.

[0048] 3) The polyamidoxime solution, porous few-layer carbon nitride and polyvinyl pyrrolidone are mixed, ultrasonically dispersed at 450W for 15 minutes, and then stirred for reaction for 12 hours to obtain a porous few-layer carbon nitride / amidoxime-based spinning solution; in this step, the mass volume ratio of the polyamidoxime solution, porous few-layer carbon nitride and polyvinyl pyrrolidone is preferably 5mL:2g:0.25g.

[0049] 4) The prepared porous few-layer carbon nitride / amidoxime-based spinning solution is passed through an electrospinning machine, and is stretched and accumulated into nanofibers by the action of electric field force. The composite nanofiber material is immersed in a 50% by volume ethanol aqueous solution preheated to 55° C., maintained at 55° C. for 24 hours, then taken out and immersed in methanol at room temperature for 7 days; finally, it is placed in a 100° C. vacuum drying oven for 16 hours to remove the polyvinyl pyrrolidone, thereby obtaining a porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure.

[0050] The electrospinning process parameters of this example are: under an environment of temperature of 30° C. and humidity of 40%, the voltage is 25 kV, the distance between the needle and the receiving plate is 20 cm, and the injection pump speed is 0.5 mL / h.

[0051] Comparative Example 1

[0052] 5 g of melamine was placed in a closed crucible and heated to 550° C. at a heating rate of 5° C. / min under air atmosphere and calcined for 2 h. After cooling, the sample was ground to obtain a yellow powder, which is bulk carbon nitride.

[0053] Comparative Example 2

[0054] 1) Mix 2g of hydroxylamine hydrochloride and 40mL of N,N-dimethylformamide (DMF) in a three-necked flask, stir mechanically at a speed of 400r / min until the hydroxylamine hydrochloride is completely dissolved, add 3g of sodium hydroxide, stir vigorously at a speed of 600r / min for 30min, add 3g of polyacrylonitrile powder, stir for 40min until the polyacrylonitrile is completely swollen, continue to stir at a speed of 400r / min for 12h at 80°C, centrifuge at a speed of 8000r / min for 3 times after the reaction is completed, and take the supernatant, which is the polyamidooxime solution;

[0055] 2) The polyamidooxime solution prepared in step 1) is stretched and accumulated into nanofibers by an electrospinning machine using an electric field force, and the nanofibers are placed in a vacuum drying oven at 50° C. for 24 hours to obtain amidoxime-based nanofibers.

[0056] The electrospinning process parameters in this comparative example are: at a temperature of 30° C. and a humidity of 40%, the voltage is 12 kV, the needle is 10 cm away from the receiving plate, and the injection pump speed is 0.2 mL / h.

[0057] Comparative Example 3

[0058] 1) In an air atmosphere, 5 g of melamine was placed in a muffle furnace and heated to 550°C at a rate of 5°C / min, and sintered for 2 h. The product was cooled to room temperature and then ground to obtain a yellow powder, which is bulk carbon nitride;

[0059] 2) 3 g of hydroxylamine hydrochloride and 40 mL of N,N-dimethylformamide (DMF) were mixed in a three-necked flask, and the hydroxylamine hydrochloride was completely dissolved by mechanical stirring at a speed of 400 r / min, and then 3 g of sodium hydroxide was added, and stirred at a speed of 600 r / min for 30 min, and then 3 g of polyacrylonitrile powder was added, and stirred at a speed of 400 r / min for 40 min until the polyacrylonitrile was completely swollen, and stirring was continued at 80° C. for 12 h. After the reaction was completed, it was centrifuged at a speed of 8000 r / min for 3 times, each time for 10 min, and the supernatant was separated as a polyamidooxime solution;

[0060] 3) The polyamidoxime solution prepared in step (2), the bulk carbon nitride prepared in step (1), and polyvinyl pyrrolidone are mixed, ultrasonically dispersed at 450W for 15 minutes, and then stirred for reaction for 12 hours to obtain a bulk carbon nitride / amidoxime-based spinning solution; in this step, the mass volume ratio of the polyamidoxime solution, the bulk carbon nitride, and the polyvinyl pyrrolidone is 5mL:1g:0.1g.

[0061] 4) The prepared bulk carbon nitride / amidoxime-based spinning solution is stretched and accumulated into nanofibers by an electrospinning machine using the action of electric field force, and then the nanofiber material is immersed in an ethanol aqueous solution (30% by volume) preheated to 45° C., maintained at 45° C. for 12 hours, then taken out, immersed in methanol at room temperature for 3 days, and finally placed in a 100° C. vacuum drying oven for 12 hours to remove polyvinyl pyrrolidone, thereby obtaining a multi-level structured bulk carbon nitride / amidoxime-based seawater uranium extraction composite material.

[0062] The electrospinning process parameters in this comparative example are: at a temperature of 30° C. and a humidity of 40%, the voltage is 12 kV, the needle is 10 cm away from the receiving plate, and the injection pump speed is 0.2 mL / h.

[0063] The adsorption performance of the adsorbent materials prepared in Examples 1-3 and Comparative Examples 1-3 was tested for uranium adsorption. The test method refers to the document "Yan BJ, Ma CX, Gao JX, et al. An Ion-Crosslinked Supramolecular Hydrogel for Ultrahigh and Fast Uranium Recovery from Seawater. [J]. Advanced Materials, 2020, 32 (10): e1906615.", as follows: 3 mg of the material to be tested was added to a conical flask containing 100 mL of a 32 mg / L uranium solution, and the pH of the solution was adjusted to seawater pH (8.2 ± 0.1) with 0.1 mol / L HCl solution and NaOH solution. It was placed on a magnetic stirrer at a constant temperature of 25 ° C for stirring and adsorption, and the speed was set to 150r / min. After the adsorption reaction was completed, azo arsenic III was used as a uranium color developer, and the uranium concentration before and after adsorption was tested using a UV-visible spectrophotometer. The adsorption capacity formula Q e =(C0-C t )V / m can be calculated to obtain the saturated adsorption capacity, where Q e : adsorption capacity at equilibrium (mg / g), C0: initial uranium concentration (mg / L), C e : uranium concentration at equilibrium (mg / L), V: volume of uranium solution (L), m: mass of adsorbent (g). The test results are shown in Table 1 below:

[0064] Table 1

[0065] sample Uranium adsorbent Saturated adsorption capacity (mg / g) Example 1 Porous few-layer carbon nitride / amidoxime-based composite fibers 482.4 Example 2 Porous few-layer carbon nitride / amidoxime-based composite fibers 450.1 Example 3 Porous few-layer carbon nitride / amidoxime-based composite fibers 436.6 Comparative Example 1 Bulk Carbon Nitride 10.8 Comparative Example 2 Amidoxime-based nanofibers 306.6 Comparative Example 3 Blocky carbon nitride / amidoxime-based composite fibers 405.2

[0066] It can be seen from Table 1 that there are differences in the saturated adsorption capacity of uranium by the porous few-layer carbon nitride / amidoxime-based composite materials of Examples 1 to 3, and the adsorption performance of the composite materials is highly correlated with the modification steps. At the same time, the saturated adsorption capacity of the multi-level porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite materials prepared in Examples 1 to 3 are significantly better than the bulk carbon nitride, amidoxime-based nanofibers, and bulk carbon nitride / amidoxime-based composite fiber adsorption materials of Comparative Examples 1 to 3.

[0067] Table 2 shows the adsorption dynamics test results of the materials prepared in Example 1 and Comparative Example 2. Figure 5The following are the uranium adsorption kinetics of the two materials. The adsorption kinetics test method can be found in the reference “Yan BJ, Ma CX, Gao JX, et al. An Ion-Crosslinked Supramolecular Hydrogel for Ultrahigh and Fast Uranium Recovery from Seawater. [J]. Advanced Materials, 2020, 32(10): e1906615.”.

[0068] Table 2

[0069] Pseudo-second-order kinetics <![CDATA[Theoretical Q e (mg·g -1 )]]> <![CDATA[k(g·mg -1 ·min -1 )]]> Example 1 520.83 <![CDATA[1.9120×10 -6 ]]> Comparative Example 2 442.48 <![CDATA[0.51349×10 -6 ]]>

[0070] Combined with Figure 5 Table 2 shows that the porous few-layer carbon nitride / amidoxime-based composite fibers of Example 1 have a higher uranium adsorption capacity and a faster uranium extraction rate than the amidoxime-based nanofibers of Comparative Example 2, especially the adsorption rate k (unit: g·mg -1 ·min -1 )) is 1.9120×10 -6 , which is significantly higher than the adsorption rate of comparative example 2 (0.51349×10 -6 The nanoscale porous structure of porous few-layer carbon nitride effectively improves the efficiency of photocatalytic reduction. After it is combined with amidoxime-based nanofibers that can specifically adsorb uranium, the constructed multi-level structure is more conducive to the circulation of adsorbed liquid, so the uranium adsorption performance of the composite material is significantly improved.

Claims

1. A method for preparing a porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure, characterized in that: The specific steps are as follows: 1) Place melamine in a sealed container and calcine at 550°C for 2 hours. After cooling, obtain blocky carbon nitride, then place it in an air atmosphere and sinter it at 550°C for 3-5 hours to obtain porous few-layer carbon nitride for later use; 2) Mix hydroxylamine hydrochloride and N,N-dimethylformamide, add sodium hydroxide and stir to react for 30-60 min; then add polyacrylonitrile powder and react until the polyacrylonitrile is completely swollen; then stir and react at 80-90 °C for 12-18 h. After the reaction is completed, centrifuge and take the supernatant, which is the polyamidooxime solution, for later use; 3) uniformly mixing the polyamidoxime solution, porous few-layer carbon nitride and polyvinyl pyrrolidone to obtain a porous few-layer carbon nitride / amidoxime-based spinning solution; 4) preparing nanofibers from the porous few-layer carbon nitride / amidoxime-based spinning solution by electrospinning, then immersing the nanofibers in an ethanol aqueous solution, taking them out and immersing them in methanol again, and drying them to obtain the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure.

2. The method for preparing the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure according to claim 1, characterized in that: In step 1), the calcination at 550°C refers to calcination at a heating rate of 5-10°C / min; the sintering at 550°C for 3-5h refers to sintering at a heating rate of 5-10°C / min.

3. The method for preparing the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure according to claim 1, characterized in that: In step 2), the mass volume ratio of hydroxylamine hydrochloride, sodium hydroxide and N,N-dimethylformamide is (2-4): (3-6): (40-50), and the mass volume ratio unit is g:g:mL; the mass volume ratio of polyacrylonitrile and N,N-dimethylformamide is (3-4): (40-50), and the mass volume ratio unit is g:mL.

4. The method for preparing the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure according to claim 1, characterized in that: In step 3), the mass volume ratio of the polyamidooxime solution, the porous few-layer carbon nitride and the polyvinyl pyrrolidone is 5:(0.5-2):(0.05-0.25); the unit of mass volume ratio is mL:g:g.

5. The method for preparing the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure according to claim 1, characterized in that: In step 3), the mixing refers to ultrasonication for 15 to 30 minutes, followed by stirring for reaction for 12 to 16 hours.

6. The method for preparing the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure according to claim 1, characterized in that: In step 4), the electrospinning process refers to spinning using an electrospinning machine at a temperature of 30°C, a humidity of 40%, a voltage of 10-25 kV, a needle of the spinning machine at a distance of 10-20 cm from the receiving plate, and a syringe pump speed of 0.2-0.5 mL / h.

7. The method for preparing the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure according to claim 1, characterized in that: In step 4), immersing the nanofibers in an ethanol aqueous solution refers to immersing the nanofibers in an ethanol solution with a volume concentration of 30% to 50% at 45 to 55° C. for 12 to 24 hours.

8. The method for preparing the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure according to claim 1, characterized in that: In step 4), the soaking in methanol refers to soaking in methanol for 3 to 7 days.

9. The method for preparing the porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure according to claim 1, characterized in that: In step 4), the drying refers to vacuum drying at 90-100°C for 12-16 hours.

10. A porous few-layer carbon nitride / amidoxime-based seawater uranium extraction composite material with a multi-level structure prepared by any method of claims 1-9.

Citation Information

Patent Citations

  • High-dispersity C3N4-based seawater uranium extraction composite material and preparation method thereof

    CN115228500A

  • Preparation method and application of a multifunctional uranium extraction material

    CN118341398B

  • Preparation of amidoximation magnetic MXene-based composite material and application of amidoximation magnetic MXene-based composite material in uranyl adsorption

    CN115945174A

  • Preparation method and application of composite nanofiber membrane based on photo-thermal enhanced uranium ion selective adsorption-photocatalysis cascade mechanism

    CN116926784A

  • Preparation method and application of multifunctional uranium extraction material

    CN118341398A

Cited By

  • Amidoximation g-C3N4 / ZrO2 adsorbent, preparation method and application thereof, and uranium extraction method

    CN117101620A

  • An amidoximated g-C3N4 / ZrO2 adsorbent, its preparation method and application, and uranium extraction method

    CN117101620B